2019
DOI: 10.1089/photob.2018.4593
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Generation Photosensitizers of PsD-007 and Hematoporphyrin Monomethyl Ether Photodynamic Therapy for Treatment of Port-Wine Stain: A Retrospective Study

Abstract: Objective: To compare the efficacy and safety of the two generation photosensitizers, PsD-007 and hematoporphyrin monomethyl ether (HMME), for photodynamic therapy (PDT) of port-wine stain (PWS). Background: Vascular-targeted PDT has shown potentially beneficial results in treating PWS; however, the efficacy and safety of various photosensitizers have not been fully investigated. Materials and methods: We retrospectively analyzed 38 patients with PWS, who were treated with one session of PsD-007-mediated (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…However, only around 10% of PWS patients achieve complete bleaching after PDL treatment and roughly 20% of lesions are resistant to PDL (5)(6)(7). As an alternative, vascular targeted photodynamic therapy (V-PDT) is considered as a safe and effective treatment for PWS, and has been used successfully to treat PWS in China since the early 1990s (8)(9)(10)(11). The side-by-side comparison studies of V-PDT and PDL for the treatment of PWS have demonstrated that V-PDT is at least as effective and safe as PDL and in some cases, superior (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…However, only around 10% of PWS patients achieve complete bleaching after PDL treatment and roughly 20% of lesions are resistant to PDL (5)(6)(7). As an alternative, vascular targeted photodynamic therapy (V-PDT) is considered as a safe and effective treatment for PWS, and has been used successfully to treat PWS in China since the early 1990s (8)(9)(10)(11). The side-by-side comparison studies of V-PDT and PDL for the treatment of PWS have demonstrated that V-PDT is at least as effective and safe as PDL and in some cases, superior (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Porphyrins, which include hematoporphyrin (Hp), are the best-studied group of photosensitizers. Hp is an organic photosensitizer, which mediates inhibition of endothelial cell proliferation in PDT and induces apoptosis [2,4,[12][13][14]. Hp has good efficacy and a low recurrence rate [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although the lesions usually involve the head and neck area, they may also occur on the trunk and extremities and may cause physical and psychosocial discomfort. Low self‐esteem difficulties in interpersonal relationships and many psychiatric problems have been reported in such patients (Ma et al, ; Wang et al, ; Zutt, ).…”
Section: Introductionmentioning
confidence: 99%